Efektivitas Pemberian Putih Telur dan Ikan Lele Terhadap Penyembuhan Jahitan Perineum pada Ibu Nifas - Bekti Yuniyanti; Mundarti; Ari Kurniawati (Universitas Ngudi Waluyo, 2026)
The Effect of Egg White and Catfish Consumption on Perineal Suture Healing in Postpartum Mothers. The postpartum period (puerperium) is a time of recovery following pregnancy and childbirth, during which complications such as uterine atony, retained placenta, and episiotomy or birth canal lacerations may occur. Nutritional factors—specifically protein, vitamins, and minerals—influence the healing of birth canal lacerations. Eggs and catfish are accessible protein sources that can be simply prepared using a blend of herbs and spices. The objective of this study was to determine the difference in effectiveness between the administration of egg white and catfish regarding the healing of perineal sutures in postpartum mothers. This study employed an experimental method with a two-group posttest-only design and was conducted at the Punggelan 2 Community Health Center (Puskesmas) in Banjarnegara Regency. The sample was selected using purposive sampling, consisting of 32 postpartum mothers with second-degree perineal sutures during February and March who had no history of diabetes mellitus or hypertension and consented to participate; 16 respondents were administered egg white and 16 were administered catfish from the first to the seventh day, with evaluations performed on the eighth day using the REEDA score. Data analysis was conducted using the Mann-Whitney test. The mean consumption was 2.56 for egg whites and 1.38 for catfish. The Mann-Whitney test results showed a p-value of 0.024 and an r-value of 0.398, with mean ranks of 20.16 for the egg white group and 12.84 for the catfish group. This indicates a significant difference in effectiveness between the two interventions regarding perineal suture healing, with catfish proving more effective for healing. Abstrak Nifas (puerperium) merupakan masa pemulihan setelah melalui masa kehamilan dan persalinan, komplikasi yang terjadi selama masa nifas seperti atonia uteri, retensio plasenta episiotomi atau laserasi jalan lahir. Salah satu faktor yang mempengaruhi penyembuhan laserasi jalan lahir yaitu faktor gizi, terutama protein, viatamin dan mineral. Telur dan ikan lele merupakan sumber protein yang mudah di jangkau dengan cara pengolahanya yang sederhana menggunakan campuran bumbu dan rempah. Tujuan untuk mengetahui perbedaan efektivitas pemberian putih telur dan lele terhadap penyembuhan jahitan perineum pada ibu nifas. Penelitian ini menggunakan metode eksperimental dengan desain two group posttest only design, dilakukan di Puskesmas Punggelan 2 Kabupaten Banjarnegara. Sampel penelitian diperoleh melalui purposive sampling yaitu ibu nifas dengan jahitan perineum dengan jahitan derajat 2 pada bulan Februari dan Maret, tidak ada penyakit DM, hipertensi, bersedia menjadi responden, sejumlah 32 responden dengan 16 responden di berikan putih telur dan 16 responden diberikan ikan lele diberikan hari pertama sampai hari ketujuh dan dievaluasi menggunakan skor REEDA hari kedelapan. Analisa data dengan uji Mann Whitney. Hasil rerata konsumsi putih telur 2,56, rerata konsumsi ikan lele 1.38. Hasil uji mann whitney menunjukkan p value 0,024, nilai r = 0,398 dengan mean rank kelompok putih telur 20,16 dan kelompok ikan lele 12.84, artinya ada perbedaan yang cukup kuat efektivitas pemberian putih telur dan ikan lele terhadap kesembuhan jahitan perineum, dimana ikan lele lebih efektif untuk menyembuhkan jahitan.